Effect of Ionizin g Radiations on Escherichia coli and Pseudomonas lundensis in Minced Beef and Chicken - Binjasass, F. M. (Biological Sciences - PJSIR, 2007)
. Escherichia coli and Pseudo111onas lunde11sis i n m i nced beef and ch icken were su bjected to rad i ation doses of 0.5, 1 .0, 1 .4, 1 .9, 2.3 and 2 9 kGy and O 3, 0.6, 0.8, 1 .0 a nd I .4 kG y, respecti ve l y, for bacteri a l i n acti vat i on. £. coli cou nt on m i nced beef was red u ced by 6 l og cycl es after a rad iation dose of 1 .4 kGy, w i th a D ,o va l ue of 0.23, w h ereas, P /und ensis cou nt i n mi nced ch i cken was red uced by 5 l og cycles after a rad iat i on dose of I .0 kG y, w i th a D, 0 va l ue of0. 1 8. £. coli an d P lundensis were sen si ti ve to rad i at i on treatm ents and re l ati vel y l ow doses of rad iation red uced th e i r n umbers si gn i ficantl y.